Cardiovascular Issues in Tyrosine Kinase Inhibitors Treatments for Chronic Myeloid Leukemia: A Review - Santoro, Marco; Mancuso, Salvatrice; Accurso, Vincenzo; Di Lisi, Daniela; Novo, Giuseppina; Siragusa, Sergio (Frontiers in Physiology, 2021)
Chronic myeloid leukemia is a myeloproliferative neoplasm driven by a fusion gene, encoding for the chimeric protein BCR-ABL, with constitutive tyrosine kinase activity. The use of tyrosine kinase inhibitors has drastically improved survival, but there are significant concerns about cardiovascular toxicity. Cardiovascular risk can be lowered with appropriate baseline evaluation, accurate choice of TKI therapy, improvement of modifiable cardiovascular risk factors through lifestyle modifications and prescription of drugs for primary or secondary prevention. Which examinations and when do they have to be scheduled? How often a TKI-treated patient should undergo which cardiology test or exam? Is there an accurate way to estimate the risk that each TKI may determine a cardiovascular adverse event in a CML patient? In few words, how can we optimize the cardiovascular risk management in CML patients before and during TKI treatment? The aim of this review is to describe cardiac and vascular toxicity of TKIs used for CML treatment according to the most recent literature and to identify unmet clinical needs in cardiovascular risk management and complications in these patients. Regarding the TKI-induced cardiovascular toxicity, the full mechanism is still unclear, but it is accepted that different factors may play different roles: endothelial damage and atherosclerosis, metabolic impairment, hypertensive effect, glomerular impairment, mast-cell disruption. Preventive strategies are aimed at minimizing cardiovascular risk when chronic myeloid leukemia is diagnosed. Cardio-oncology units in specialized hematology centers may afford a personalized and multidisciplinary approach to the patient, optimizing the balance between treatment of the neoplasm and management of the cardiovascular risk.